Asian Currency Baskets: A Useful Surveillance Tool? - ADAMS, Charles (Institutional Knowledge at Singapore Management University, 2007)
This paper considers whether an intra-regional currency basket and the associated divergence indicators could play a useful role in official exchange rate surveillance. Recently, proponents of an Asian currency basket have referred to the role the European Currency Unit played in constructing exchange rate divergence indicators as evidence of the usefulness of intra-regional currency baskets for exchange rate monitoring. The paper shows that such indicators have a number of features that can lead to them obscuring underlying changes in exchange rates and that the signals they emit will often be difficult to interpret. In addition, the use of regional currency baskets for surveillance can lead to potentially serious N-1 problems in circumstances when there is not agreement about which regional currencies will be the anchor currencies. An intra regional currency basket and the associated divergence indicators will be a rudderless beacon for surveillance unless there is agreement about anchors.